Avatar of the self: Governing meta-body elaborated based on embodiments of consumption - Melo Moura, Bruno; Maranhão de Souza-Leão1, André Luiz (Review of Business Management, 2024)
Purpose – The aim of the current study is to investigate how consumer performativity is enacted through embodiment transformation, based on the theoretical elaboration of the body in three dimensions, namely: resistance, utopia and desire. Theoretical framework – Based on previous literature, the study proposes a theoretical framework when embodiment transformations – i.e., politics, pleasures, and affects – overlap through consumer performativity, evoking Foucauldian concepts to understand the dispositif sustained in a consumption ethos. Design/methodology/approach – The study was conducted by investigating the cosplay practice based on the use of an ethnographic Foucauldian genealogy. Findings – The results evidenced three consumption embodiments based on dispositifs circumscribed amidst pairs of body dimensions: redemption, related to politics; reward, regarding pleasure; and rapport, about affection. Practical & social implications of research – Presumably, these representations are evidence of an attempt to improve the body that represents the best way to experience this consumption ethos, which is herein called the “avatar of the self”: a governing meta-body used to mediate consumption experiences through performativities. Originality/value – Avatar of the self is an interpretation of the theoretical generalization of phenomena of consumption embodiment through performativities.